Prevalence of foot affections of buffaloes (Bubalus bubalis) with their associated risk factors in Rupandehi, Nepal - Ashwini Kumar Jha,; Suman Kumar Singh,; Anwar Zaib Khan,; Amar Nath Chaudhary,; Ganga Prasad Yadav,; Md Mahfuzul Haque, (Research in Agriculture Livestock and Fisheries, 2025)
Buffaloes play an important role in the milk and meat industry in Nepal. Foot affections have a direct impact on production and reproductive performance of the animals. This study was carried out to determine the prevalence of foot affections of buffaloes and to explore the risk factors associated in Siddharthanagar municipality, Rupandehi. Foot affections were physically investigated and examined from October 2022 to January 2023 A.D. Purposive sampling from different free rearing grazing systems and stall-feeding grazing systems was done. The farmers were asked questionnaire along with physical and clinical examination of buffaloes was performed. The cases were classified on the basis of age, sex, floor system, grazing system and limbs involved. Out of 811 buffaloes examined, 52 cases were found with foot affections, resulting in overall prevalence of 6.41%. The foot affections found were Overgrowth of Hoof (4.9%), Corkscrew (0.99%), Digital Dermatitis (0.25%), and Scissor claw (0.25%). The higher prevalence was observed in the age group greater than two years. The females had higher occurrence of foot affections. Stall fed buffaloes had shown more affections than free range grazed buffaloes. Buffaloes kept in concrete floor had shown more affections in comparison to mud floor. The higher occurrence of foot affections was observed in hindlimbs and in medial claws. It is recommended that further studies are required to address the foot affections in livestock and their management. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 73-83